A systematic review and meta-analysis of the diagnostic accuracy of rapid immunochromatographic assays for the detection of dengue virus IgM antibodies during acute infection. - Blacksell, S; Doust, J; Newton, P; Peacock, S; Day, N; Dondorp, A (2006)
A meta-analysis of rapid (